2007
DOI: 10.1139/z07-027
|View full text |Cite
|
Sign up to set email alerts
|

Winter selection of roost sites by ruffed grouse during daytime in mixed nordic-temperate forests, Quebec, Canada

Abstract: We determined the categories of roost sites used by ruffed grouse ( Bonasa umbellus (L., 1766)) during daytime in winter from 245 radiotelemetric locations of 26 adult females. We conducted our study in the Réserve faunique de Portneuf, located in a mixed nordic-temperate softwood–hardwood forest in Quebec, Canada. We evaluated the effects of weather, snow, and habitat variables on the incidence of snow burrowing, tree roosting, and on-snow roosting using mixed multinomial models, ANOVA, and logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…loss by roosting in snow burrows (Andreev 1999) where the ambient temperature usually exceeds their lower critical temperature (Marjakangas et al 1984). Snow burrowing has, therefore, a primary importance for winter survival and could be favored by compact snow as Blanchette et al (2007) showed for the ruffed grouse (Bonasa umbellus) in Québec. Alternatively, the effect of temperature range on growth rate in our models may have been confounded by the amount of precipitation during December in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…loss by roosting in snow burrows (Andreev 1999) where the ambient temperature usually exceeds their lower critical temperature (Marjakangas et al 1984). Snow burrowing has, therefore, a primary importance for winter survival and could be favored by compact snow as Blanchette et al (2007) showed for the ruffed grouse (Bonasa umbellus) in Québec. Alternatively, the effect of temperature range on growth rate in our models may have been confounded by the amount of precipitation during December in this study.…”
Section: Discussionmentioning
confidence: 99%
“…During the winter, black grouse reduce heat loss by roosting in snow burrows (Andreev ) where the ambient temperature usually exceeds their lower critical temperature (Marjakangas et al ). Snow burrowing has, therefore, a primary importance for winter survival and could be favored by compact snow as Blanchette et al () showed for the ruffed grouse ( Bonasa umbellus ) in Québec.…”
Section: Discussionmentioning
confidence: 99%
“…We expected the effect of snow to differ depending on whether snow burrowing was possible, so we quantified personality and plasticity separately for snow depths above and below 15 cm; this cut-off is generally considered the minimum depth needed for grouse to snow burrow [46,59]. We defined personality in selection for shallow snow as the mean probability of use below 15 cm of snow for each individual (SSE < 15 M ), and plasticity in selection for shallow snow as the change in probability of use between the minimum snow depth available to the individual and 14.9 cm (ΔSSE < 15).…”
Section: (E) Survival Modelsmentioning
confidence: 99%
“…Negative effects have also been shown for other less-studied taxa, such as amphibians (Waldick et al 1999), small mammals (Moore and Allen 1999), and arthropods (Magura et al 2000). Grouse use conifers for roosting or thermal protection during winter (Blanchette et al 2007), but otherwise avoid pure conifer stands (Rusch et al 2000;Endrulat et al 2005). In contrast to plantations, early successional forests or shrubdominated habitats, like those found on abandoned farm fields, are important for many game species and their predators (Dessecker and McAuley 2001;Litvaitis 2001;Fuller and DeStefano 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we quantified differences between the two types of habitat, as the value of the abandoned farm fields had never been estimated for grouse in the region. Grouse use conifer stands for roosting during winter (Thompson and Fritzell 1988;Blanchette et al 2007), but will generally avoid pure conifer stands during the drumming season because they provide hunting perches and nesting areas for predators (Gullion and Alm 1983). Consequently, we hypothesized that the transformation of old fields with a deciduous and heterogeneous shrub layer into a homogenous habitat dominated by conifer plantations would reduce grouse habitat quality and lead to lower population densities in these habitat types.…”
Section: Introductionmentioning
confidence: 99%